Lebanon Is Burning and Other Dispatches - Al-Saadi, Yazan (Pennsylvania State University Press, 2024)
"A collection of comic dispatches drawn by various cartoonists from the Middle East, underscoring how the multiple struggles in the region are linked to a grander fight for sustainable, just futures for all"--